Tunable laser in Ytterbium-doped Y2O3 nanoparticle optical fibers - Lim, Kok-Sing (2013)
We investigate tunability of fiber lasers in ytterbium-doped Y2O3 nanoparticle fibers. A net emission cross section constructed from the spectroscopic measurements reveals the feasibility of tunable laser operation in the fiber. Broad tuning ranges of 1040-1108 nm and 1025-1090 nm are demonstrated in 6- and 3-m-long fibers, respectively, with 76% of maximum efficiency.